Virtual Handover of Patients in the Pediatric Intensive Care Unit During the Covid-19 Crisis - Temsah, Mohamad-Hani (J Multidiscip Healthc, 2021)
OBJECTIVE: A key measure to mitigate coronavirus disease 2019 (COVID-19) has been social distancing. Incorporating video-conferencing applications in the patient handover process between healthcare workers can enhance social distancing while maintaining handover elements. This study describes pediatric intensive care unit (PICU) physicians’ experience using an online video-conferencing application for handover during the COVID-19 pandemic. DESIGN: Qualitative content analysis. SETTING: PICU at a university hospital in Riyadh, Saudi Arabia. SUBJECTS: PICU Physicians. INTERVENTIONS: Due to the pandemic, the hospital’s PICU used Zoom(®) as a remote conferencing application instead of a face-to-face handover. Following institutional review board approval, data were collected over two weeks (1 Jul 2020 to 14 Jul 2020). MEASUREMENTS: An online survey was conducted using open-ended questions to capture demographic data and the perceived efficacy of remote handovers. Thematic framework analysis process included open coding, creating categories, and abstraction. MAIN RESULTS: All 37 PICU physicians who participated in the handover completed the survey. The participants comprised six attendings, nine specialists, and 22 residents. While 20 (54.1%) physicians reported attending 1–5 Zoom handovers by the time of the study, some (n. 6, 16.2%) had more than ten virtual handovers. They had variable previous teleconferencing experiences. Most physicians (78.4%) were comfortable conducting a remote handover. Most found that Situation–Background–Assessment–Recommendation handover elements were properly achieved through this remote handover process. The perceived advantages of online handover included fewer interruptions, time efficiency, and facilitation of social distancing. The perceived disadvantages were the paucity of nonverbal communication and teaching during virtual meetings. CONCLUSION: Video-conferencing applications for online handovers could supplement traditional face-to-face intensive care unit patient handover during outbreaks of infectious diseases. The use of video streaming and more emphasis on teaching should be encouraged to optimize the users’ experience.